THE EAST IN THE WORKS OF RUSSIAN-FRENCH TRAVELER, PRINCESS LYDIA PASHKOVA: PUSHING THE BOUNDARIES OF ORIENTALIST DISCOURSE - E. Moiseeva (Гуманитарные и юридические исследования)
The article studies the image of the East in the travelogues of the Russian Princess, traveler Lidia Pashkova, published in France and Russia in the last third of the XIX century. The notes on travel to the Ottoman Empire and the Far East are studied. The article attempts to identify the narrative that runs both in line and contrary to the orientalist tradition. A characteristic feature of the notes about Lydia Pashkova's travels was her attention to the history and cultural heritage of those countries where she had to visit, which is typical both for orientalist discourse and traditions of studying the East in the West, and for the image of an "inquisitive observer". The humanistic character of Pashkova's travelogues differs them from traditional orientalist discourse and outputs beyond the Eurocentric narrative. It should be noted that the Imperial ideas had an impact on Pashkova. This refers to the recognition of the civilizing mission of the West. However, awareness of the value of Western civilization and recognition of the civilizing mission of the West did not mean the automatic recognition of the right of the West to own the countries of the East. Much attention is paid to the study of the images of local residents. The "hybrid" nature of Pashkova's travelogues is stressed, the problems of history, culture, ethnography, economy, geography are highlighted equally. Travelogues of Princess Lydia Pashkova are characterized by a real interest in different aspects of life; they do not feature the search for exotics in the East.